Soft Skills as Pillars of Success in Educational Leadership: An In-Depth Analysis - Moses Adeleke Adeoye (PAEDAGOGIA, 2025)
In the dynamic realm of educational leadership, the significance of soft skills has become increasingly recognised as essential to fostering effective and collaborative environments. This research discourse employs a systematic review approach to explore these competencies' critical role in enhancing leadership effectiveness. A comprehensive search of academic databases was conducted using relevant keywords related to soft skills and educational leadership, adhering to strict inclusion and exclusion criteria to ensure the quality of selected studies. The findings reveal that essential soft skills such as communication, motivation, conflict management and trust-building are critical in influencing not only educational leaders' performance but also educational institutions' overall success. The analysis identifies common themes across various studies, highlighting how leaders who excel in these areas create inclusive, engaging environments that promote collaboration and innovation. Furthermore, the research underscores the necessity for educational institutions to integrate soft skills training into leadership development programs, thereby equipping future leaders with the tools to navigate complex challenges effectively. In conclusion, this discourse emphasises that soft skills are not just ancillary traits but foundational elements of successful educational leadership. By prioritising these competencies, educational leaders can cultivate dynamic learning communities that empower both educators and students, ultimately enhancing the educational experience and outcomes for all stakeholders involved